The Brain Mechanisms Underlying the Perception of Pungent Taste of Capsaicin and the Subsequent Autonomic Responses - Kawakami, Shinpei; Sato, Hajime; Sasaki, Akihiro T.; Tanabe, Hiroki C.; Yoshida, Yumiko; Saito, Mitsuru; Toyoda, Hiroki; Sadato, Norihiro; Kang, Youngnam (Frontiers in Human Neuroscience, 2016)
In a human fMRI study, it has been demonstrated that tasting and ingesting capsaicin activate the ventral part of the middle and posterior short gyri (M/PSG) of the insula which is known as the primary gustatory area, suggesting that capsaicin is recognized as a taste. Tasting and digesting spicy foods containing capsaicin induce various physiological responses such as perspiration from face, salivation and facilitation of cardiovascular activity, which are thought to be caused through viscero-visceral autonomic reflexes. However, this does not necessarily exclude the possibility of the involvement of higher-order sensory-motor integration between the M/PSG and anterior short gyrus (ASG) known as the autonomic region of the insula. To reveal a possible functional coordination between the M/PSG and ASG, we here addressed whether capsaicin increases neural activity in the ASG as well as the M/PSG using fMRI and a custom-made taste delivery system. Twenty subjects participated in this study, and three tastant solutions: capsaicin, NaCl and artificial saliva (AS) were used. Group analyses with the regions activated by capsaicin revealed significant activations in the bilateral ASG and M/PSG. The fMRI blood oxygenation level-dependent (BOLD) signals in response to capsaicin stimulation were significantly higher in ASG than in M/PSG regardless of the side. Concomitantly, capsaicin increased the fingertip temperature significantly. Although there was no significant correlation between the fingertip temperatures and BOLD signals in the ASG or M/PSG when the contrast [Capsaicin–AS] or [Capsaicin–NaCl] was computed, a significant correlation was found in the bilateral ASG when the contrast [2×Capsaicin–NaCl–AS] was computed. In contrast, there was a significant correlation in the hypothalamus regardless of the contrasts. Furthermore, there was a significant correlation between M/PSG and ASG. These results indicate that capsaicin increases neural activity in the ASG as well as the M/PSG, suggesting that the neural coordination between the two cortical areas may be involved in autonomic responses to tasting spicy foods as reflected in fingertip temperature increases.